Hyperfine fields of probe atoms on the (001) surface of Ni - P. Mavropoulos; N. Stefanou; B. Nonas; R. Zeller; P.H. Dederichs (PHILOSOPHICAL MAGAZINE B-PHYSICS OF CONDENSED MATTER STATISTICAL MECHANICS ELECTRONIC OPTICAL AND MAGNETIC PROPERTIES, 1998)
We present first-principles calculations of the electronic structure and hyperfine fields of 3d and 4sp impurities on the (001) surface of Ni. The calculations are based on the local-spin-density-functional theory and employ a Korringa-Kohn-Rostoker Green's function method for impurities at surfaces. The systematic behaviour obtained for the hyperfine fields of the 4sp adatoms or impurities in the first surface layer is completely different from that found in the bulk. Instead of a single maximum with a very large hyperfine-field value at about the end of an sp series, the adatoms exhibit two maxima with a pronounced minimum in between. This behaviour can be traced back to the reduced coordination number of the adatoms which leads to a much smaller relative splitting of the bonding and antibonding peaks, and to the lower symmetry at the surface which results in an on-site s-p(z) hybridization. The hyperfine fields found for the 3d impurities at the surface are determined basically by the ferromagnetic or antiferromagnetic coupling of the local impurity moment to the substrate magnetization and are therefore more or less similar to those for bulk impurities.